2018
DOI: 10.22159/ajpcr.2018.v11i3.23384
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation the Toxicity Mechanism of Zinc Oxide Nanoparticle Using Molecular Docking Approach With Proteins

Abstract: Objective: At present, toxicological tests are resource-intensive, time-consuming and require a large pool of animal models for toxicity assessment. To speed up the toxicity evaluation and to reduce animal suffering during toxicity assessment, the use of alternative methods including computational models is in high demand. The computational toxicity prediction methods are very helpful for the regulatory bodies to quickly assess the health impact of nanomaterial materials. In the present work, we have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Thus far, computational modeling has utilized the protein crystal structure to investigate the cytotoxic effects and potential risks associated with functionalized NPs in many fields of nanotechnology [ 72 , 73 , 74 , 75 ]. For instance, cytochrome P450 (CYP) is an important enzyme system for drug metabolism.…”
Section: Category Of In Silico Modelsmentioning
confidence: 99%
“…Thus far, computational modeling has utilized the protein crystal structure to investigate the cytotoxic effects and potential risks associated with functionalized NPs in many fields of nanotechnology [ 72 , 73 , 74 , 75 ]. For instance, cytochrome P450 (CYP) is an important enzyme system for drug metabolism.…”
Section: Category Of In Silico Modelsmentioning
confidence: 99%
“…P38 (PDB ID: 3W8Q) had the highest binding affinity (−8.81 kcal/mol), while IL-1B (PDB ID: 1I1B) had the lowest (−3.23 kcal/mol). Furthermore, ZnO NPs were studied as α-glucosidase enzyme inhibitors, a popular target for the management of diabetes [ 137 ]. When ZnO NPs were generated at the 500 °C calcination temperature, they had the strongest binding energy to this enzyme (−13.64 kcal/mol), with a size of around 32 nm [ 126 ].…”
Section: Analysis Of Biomacromolecule–np Interactions Using Molecular...mentioning
confidence: 99%
“…It was observed that ZnO-NP (zinc oxide nanoparticles) has a strong binding affinity with NF-κB, suggesting a potential interaction between these nanoparticles and the protein. This interaction may have implications for the regulation of inflammation and immune responses in the body [7].…”
Section: Introductionmentioning
confidence: 99%